Topos of death in the novel «The lovely bones» by A. Sebold - Zelezinskaya, Natalia S. (Journal of the Belarusian State University. Philology, 2022)
A. Sebold not only makes the motif of death central in the novel «The lovely bones», but also presents the idea of death in the unusual for American realistic children’s, teenage and youth literature of the second half of the 20th – 21st centuries religious context. Christian cultural attitudes and the medieval picture of the world influence not only the semantics of this motif, but also the structural organisation of the text space. Such topos as a basement, a dugout, a littered mine, a home, a school, a town and a forest are considered. Topos of death in a horizontal and vertical section are analysed from the perspective of a three-part space (Yu. M. Lotman, V. N. Toporov). A significant role in the interpretation of the semantics and pragmatics of topos of death is played by the dichotomies of one’s own – someone else’s, suffering – bliss, earth – heaven, hell – paradise, attractive – boring, etc. To implement them, A. Sebold appeals to the medieval mentality, as well as to the concept of purgatory of early modern period. The axiological potential of the novel and the ability of a modern young person to accept the reality of the world in all its beauty and horror are explored. Awareness of one’s separateness and selfhood, resignation to the irreversibility of death, recognition of the existence of a «world without me» and finding joy for another person predetermine the finale of the novel – the heroine’s metaphorical transition from purgatory to paradise. The connection between the pragmatics of the novel and the latest theories of modern philosophy is indicated.